Persepsi Masyarakat Dalam Membuka Lahan Dan Faktor Pemicu Kebakaran Lahan Provinsi Riau - Rindukasih Bangun; Rosnita; Herlon; Pebrian; Oktari; Ratna Megawati (Badań Perencanaan Pembangunan Dearth, Penelitian dań Pengembangan Provinsi Riau, 2017)
Land and forest fires in Riau Province mostly begins by human activity. The purpose of the study is 1) Describe the perception of the public in using and managing land by burning and without burning, 2) Knowing the supporting factors that cause fire, 3) Reviewing community and institutional efforts in prevention and control fire. Location of study conducted in four districts, Kepulauan Meranti District, Rokan Hulu District, Pelalawan District, and Kampar District. Implementation of the study using survey methods and Rapid Rural Apraisal (RRA). The result of this study are 1) The public perception of land clearing by burning due to a) The fee required in technical land clearing by burning relatively cheap when compared to the way of land clearing without burning, b) Technical land clearing does not need many labors, c) The ashes of burnt remains are useful to fertilize the soil, d) Activity land clearing by burning is a culture or tradition that occur for generations, 2). Causative factors of land and forest fires are: a) Aspects of biophysical, b) Climatic conditions, c) Physical conditions, d) Economic conditions (the level of forest and land dependence is very high), e) Social and cultural conditions (community social capital is still quite lacking in terms of awareness of the impact and dangers of fire use), 3). Efforts to prevent and control forest and land fire has been done by the community and government institutions.